EVALUATING THE IMPLEMENTATION OF GEOGRAPHICAL INDICATION PROTECTION FOR BATIK LASEM: CHALLENGES AND OPPORTUNITIES - Adityayoga, Adityayoga (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
This study evaluates the implementation of Geographical Indication (GI) protection for Batik Lasem, focusing on its impact, challenges, and potential improvements. While GI certification has bolstered artisans' confidence by providing legal safeguards, limited understanding of its protection scope such as motif preservation and violation reporting procedures—hinders its effectiveness. Artisans express concerns over plagiarism and inadequate support in addressing violations, highlighting the need for targeted education and clear reporting mechanisms. Using qualitative methods, including interviews with artisans and MPIG members and document analysis, the research identifies gaps in community knowledge and enforcement practices. Findings emphasize the necessity of intensive training and stronger collaboration between MPIG, government, and artisans to optimize GI's protective function. By enhancing community participation and refining implementation strategies, this study offers actionable recommendations to strengthen Batik Lasem’s cultural heritage and market positioning, ensuring sustainable benefits for the local ecosystem.